The Reinforcement of the ‘Dowry for Groom’ Tradition in Customary Marriages of West Sumatra’s Pariaman Society - Busyro, Busyro; Burhanuddin, Nunu; Muassomah, Muassomah; Saka, Putri Ananda; Wafa, Moh Ali (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
In contrast to the customary mahar or dowry system in typical Indonesian marriages, West Sumatra's Minangkabau people in Pariaman practice a unique ‘dowry for groom’ tradition, in which the bride pays a dowry to the bridegroom based on his social status. Payment is adjusted according to the social status of the man and is a must for the marriage to take place. This paper aims to examine the persistence and strengthening of the ‘dowry for groom’ tradition in the Pariaman Muslim community in West Sumatra by focusing on three main issues, namely the practice of ‘dowry for groom’ in the Pariaman community; factors that make the ‘dowry for groom’ tradition survive among Pariaman Muslims in the midst of the swift currents of modernization and globalization; and the mechanism of social reproduction of the 'dowry for men' tradition in the Pariaman community. The study is an empirical legal research using sociological theory as an analytical tool. Data is collected through interviews, observation and literature studies. The findings reveal that the reinforcement of the 'dowry for groom' tradition in Pariaman society is supported by several fundamental factors, including the widespread practice and support from the community, religious and traditional leaders, the local government, and the younger generation. The 'dowry for groom' tradition in Pariaman reflects the values of Muslim identity, such as adherence to religious teachings by finding husbands for daughters and maintaining a spirit of mutual aid, while also protecting the Minangkabau institution of ninik mamak (elders) and strengthening women's position as the true